The Complex Interplay of EU-China and EU-HKSAR Relations - Gough, Antonia (UI Scholars Hub, 2018)
Due to a unique colonial history, Hong Kong today operates under the “One Country, Two Systems” framework. In the years immediately following the handover, it was generally thought that this was working quite well. In recent years, however, tensions have arisen within the “One Country, Two Systems” model, most notably including the 2014 Umbrella Movement, the imprisonment of student protesters and various notable incidents like the disappearance of five book publishers. This article aims to uncover how consistent the EU is in promoting democratic norms in its relations with the HKSAR. Using discourse analysis of relevant EU documents, the article explores two things. Firstly, to investigate whether these tensions lead to potential (in)consistencies between what the EU says and how it in fact acts regarding disputes between Hong Kong and China. Secondly, since a large part of EU discourse stresses the promotion of values and norms such as democracy, this article analyses the consistency of this discourse.